Is dibotermin alfa a cost-effective substitute for autologous iliac crest bone graft in single level lumbar interbody spine fusion?. (2nd November 2015) - Svedbom, Axel; Paech, Daniel; Leonard, Catherine; Donnell, David; Song, Fujian; Boszcyk, Bronek; Rothenfluh, Dominique A.; Lloyd, Andrew; Borgman, Benny
Abstract: Objectives: To evaluate the cost-effectiveness of dibotermin alfa compared with autologous iliac crest bone graft (ICBG) for patients undergoing single level lumbar interbody spinal fusion in a UK hospital setting. Methods: An individual patient data (IPD) meta-analysis of six randomized controlled clinical trials and two single arm trials compared dibotermin alfa on an absorbable collagen implantation matrix (ACIM) ( n = 456) and ICBG ( n = 244) on resource use, re-operation rates, and SF-6D (Short form 6-dimension) health utility (total N = 700). Failure-related second surgery, operating time, post-operative hospital stay, and quality-adjusted life years (QALYs) derived from the IPD meta-analysis were included as inputs in an economic evaluation undertaken to assess the cost-effectiveness of dibotermin alfa/ACIM versus ICBG for patients undergoing single level lumbar interbody spinal fusion. A four year time horizon and the United Kingdom (UK) National Health Service (NHS) and Personal Social Services (PSS) perspective was adopted in the base case, with sensitivity analyses performed to gauge parameter uncertainty. Results: In the base case analysis, patients treated using dibotermin alfa/ACIM (12 mg pack) accrued 0.055 incremental QALYs at an incremental cost of £737, compared with patients treated with ICBG. This resulted in an incremental cost-effectiveness ratio (ICER) of £13, 523, indicating that at a willingness-to-pay threshold of £20, 000, dibotermin alfa/ACIM is a cost-effective intervention relative to ICBG from the NHS and PSS perspective. Conclusions: In a UK hospital setting, dibotermin alfa/ACIM is a cost-effective substitute for ICBG for patients who require lumbar interbody arthrodesis.